Changes in sensorimotor functions after spinal lesions evaluated in terms of long-latency reflexes. Issue 12 (December 1987) - Ackermann, H; Diener, H C; Dichgans, J
Abstract : Lesions of the central afferent and efferent pathways cause onset-delays of long-latency EMG responses from anterior tibial muscle after passive dorsiflection of the ankle joint in standing subjects. In 23 patients with spinal tumour or cervical stenosis and clinical signs of a medullary lesion, short-, medium- and long-latency EMG responses from distal leg muscles after ankle dorsiflection were recorded prior to and after surgical intervention. Fifteen of the patients were re-examined between 1 and 2 years after surgery. The results of the follow-up study support the hypothesis of a supraspinal pathway for long-latency EMG responses in distal leg muscles and show their significance as a quantitative measure of sensorimotor functions.